Large-closed-pore hard carbon negative electrode material, preparation method and sodium ion battery thereof
By using large closed-cell hard carbon materials prepared by using biomass cotton straw and activator, the problem of insufficient performance of the negative electrode material of sodium ion battery is solved, and high energy density and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411345182.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Existing sodium ion battery negative electrode materials are insufficient, especially high-energy density and low-cost high-performance negative electrode materials are difficult to achieve. Graphite is unstable due to the unstable binary graphite intercalation compound formed by the embeddedness of sodium ions, which limits the energy density of sodium ion batteries. Improvement.
Using biomass cotton straw as raw material, the activation reaction is carried out by mixing salt KOH and K2CO3 activators, combined with preoxidation process and chemical vapor deposition method, a hard carbon negative electrode material with large closed pore diameter is prepared, and the oxygen-containing graphite domain sheet is at high temperature. During the process, the stacking of graphite domains is prevented, the pore shrinkage is hindered, and the opening pores with large pore sizes are blocked through chemical vapor deposition.
A rich number of closed pores and a large closed pore size are achieved, providing more sodium ion storage sites and storage space, significantly improving electrochemical performance and specific capacity of the platform area, and optimizing kinetic activity.
Smart Images

Figure CN119218975A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy materials, and in particular to a method for preparing a large closed-pore hard carbon negative electrode material and a sodium ion battery. Background Art
[0002] The rapid development of modern society is inseparable from the massive consumption of energy, while the excessive use of traditional chemical energy has led to increasingly serious resource depletion and environmental pollution problems. Finding effective and low-cost energy storage solutions has attracted widespread attention from the society, so exploring emerging green energy has become a hot research direction in today's society. Lithium-ion batteries (LIBs) are widely used in many fields such as energy storage and power batteries due to their excellent energy density and outstanding cycle performance. However, the cost of raw materials for lithium-ion batteries and the fact that lithium supply is limited and unevenly distributed globally have brought difficulties to the larger-scale application of lithium-ion batteries. In contrast, sodium-ion batteries (SIBs) show great potential in large-scale energy storage systems due to the sufficient availability of sodium resources and their low cost-effectiveness. At present, a large number of sodium-ion battery positive electrode materials have been developed, but the lack of high-performance negative electrode materials has greatly hindered the further improvement of the energy density of sodium-ion batteries. Graphite is a commercial negative electrode material for lithium ions. Since sodium ions are embedded in graphite to form binary graphite intercalation compounds, which are thermodynamically unstable, graphite has limited sodium storage capacity. Therefore, the research of high-performance negative electrodes with high capacity and low cost is the main challenge currently faced.
[0003] To date, hard carbon, as a non-graphitizable carbon, has become the most likely negative electrode material for sodium-ion batteries to be commercialized. Hard carbon has a randomly distributed turbostratic microstructure, a large interlayer spacing (over 0.37 nm), and closed nanopores. The charge and discharge curve of hard carbon sodium storage is divided into a slope region above 0.1 V and a platform region below 0.1 V. Related studies have shown that in the low-voltage platform region, the filling of sodium ions in closed pores is the main mechanism for storing sodium. Therefore, to achieve more platform capacity below 0.1 V, closed pores with as abundant and larger pore sizes as possible are required. For example, Titirici et al. prepared hard carbon at different temperatures and obtained hard carbon negative electrodes with different pore sizes. Electrochemical tests showed that the sample calcined at 1500°C showed the highest platform capacity (216 mAh g -1). It is proved that the capacity of the platform area is proportional to the closed pore diameter. In the article Oxygen-driven closing pore formation in coal-based hard carbon for low-voltage rapid sodium storage (Chemical Engineering Journal, 2024, 493, 152389), Ma et al. used coal as a precursor to change the growth mode of graphite domains through pre-oxidation and obtained hard carbon materials rich in closed pores, but ignored the effect of the activity and disorder of the precursor on the closed pore diameter.
[0004] Therefore, how to adopt a convenient, environmentally friendly, and low-cost strategy to obtain hard carbon negative electrode materials that meet the requirements of high energy density sodium ion batteries is one of the research focuses in the field of hard carbon negative electrode materials. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a large closed-pore hard carbon negative electrode material. The present invention uses biomass cotton stalks as raw materials, and adopts a mixed salt of KOH and K 2 CO 3 As an activator, a hard carbon active precursor is prepared through an activation reaction. A pre-oxidation process is further used to graft oxygen onto the graphite domain sheets of the hard carbon active precursor, and then a hard carbon negative electrode material with a larger closed pore size is prepared by combining high-temperature crystal transformation and chemical vapor deposition methods. The oxygen-containing graphite domain sheets prevent the stacking of graphite domains during the high temperature process and hinder the shrinkage of the pores. The large-diameter open pores are closed by plugging the pores through chemical vapor deposition. The hard carbon negative electrode material has a rich number of closed pores and a larger closed pore size, which is conducive to the storage of more sodium ions and achieves excellent electrochemical performance.
[0006] In order to achieve the above-mentioned object of the invention, the technical solution of the present invention is as follows:
[0007] The present invention provides a method for preparing a large closed-pore hard carbon negative electrode material, comprising the following steps:
[0008] (1) Weighing an appropriate amount of washed and dried cotton stalks, crushing them, and sieving them;
[0009] (2) Mix the sieved cotton straw with KOH and K 2 CO 3 The activators are uniformly mixed according to a certain mass percentage;
[0010] (3) The mixed material obtained in step (2) is subjected to activation reaction in a tube furnace under the protection of argon or nitrogen atmosphere, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use;
[0011] (4) spreading the hard carbon active precursor obtained in step (3) in a uniform thin layer on the bottom of the porcelain boat, placing it in a tube furnace, and performing low-temperature oxidation in an air or oxygen atmosphere to obtain a pre-oxidized hard carbon active precursor;
[0012] (5) placing the pre-oxidized hard carbon active precursor obtained in step (4) in a high-temperature furnace and performing high-temperature crystal transformation in an argon or nitrogen atmosphere to obtain a hard carbon material with a large open pore size; (6) subjecting the hard carbon material with a large open pore size obtained in step (5) to chemical vapor deposition in a mixed gas atmosphere of carrier gas argon and carbon-containing gas to prepare a hard carbon negative electrode material with a large closed pore size.
[0013] Preferably, the particle size of the cotton straw powder in step (1) is 2-20 microns, preferably 5-10 microns, to ensure that the prepared hard carbon negative electrode material has a high tap density and fast kinetics.
[0014] Preferably, in step (2), the mass percentage of cotton straw to activator is 25%-100%, to ensure the activation degree of hard carbon active precursor, wherein KOH and K 2 CO 3 The mass ratio is 1:1.
[0015] Preferably, the temperature of the activation reaction in step (3) is 700-850° C. (preferably 750° C.), the heating rate is 5-10° C. / min, and the reaction time is 2-5 h, to ensure that the cotton straw is not over-activated.
[0016] Preferably, the pre-oxidation temperature in step (4) is 150-300° C. (preferably 200° C.) to ensure a suitable oxygen content in the hard carbon active precursor.
[0017] Preferably, in step (4), the pre-oxidation heating rate is 5-10°C / min, and the pre-oxidation time is 12-24h.
[0018] Preferably, the pre-oxidation atmosphere in step (4) is air, oxygen, or a mixture of air and oxygen with a certain oxygen content (oxygen content greater than 10%).
[0019] Preferably, the reaction temperature of the high temperature reaction in step (5) is 1200-1600° C., the reaction time is 4-6 hours, and the heating rate is 5-10° C. / min, so as to adjust the graphite domain microstructure and close some open pores to form closed pores.
[0020] Preferably, the carbon-containing gas in step (6) includes toluene, benzene, styrene, or any combination of one or two or more.
[0021] Preferably, in step (6), the gas flow rate of the carrier gas argon or nitrogen is 150-300 mL / min, and the volume concentration of the carbon-containing gas in the mixed gas is not less than 5%, so as to ensure full closure of the opening.
[0022] Preferably, in the step (6), the chemical vapor deposition coating reaction temperature is 600-900°C (preferably 700°C), the heating rate is 10°C / min, and the deposition time is 1-3h. The deposition amount can be regulated by controlling the reaction temperature and reaction time to ensure that all openings are fully closed.
[0023] Preferably, the specific surface area of the large closed-pore hard carbon negative electrode material in step (6) is 2-10 m 2 / g.
[0024] The present invention also provides a sodium ion battery hard carbon negative electrode material, which is characterized in that the hard carbon negative electrode material with large closed pores is prepared by any combination of the above technical solutions through activation-pre-oxidation-pore blocking.
[0025] The present invention adopts the above-mentioned large closed-pore hard carbon negative electrode material to prepare electrode plates and assemble them into sodium ion batteries.
[0026] The invention discloses a method for manufacturing a button battery.
[0027] Beneficial Effects
[0028] 1. The hard carbon active precursor prepared by the present invention is prepared using cotton straw as raw material by an activation method which is simple, low-cost and can be used for large-scale production.
[0029] 2. The hard carbon negative electrode material with large closed pore size prepared by the present invention uses a hard carbon active precursor as a matrix material, and prepares a hard carbon negative electrode material with large open pore size through pre-oxidation treatment, and further obtains a hard carbon negative electrode material with large closed pore size through chemical vapor deposition.
[0030] 3. The hard carbon negative electrode material with large closed pore size prepared by the present invention has the following advantages: oxygen is grafted onto the graphite domain sheet by pre-oxidation, and the oxygen-containing graphite domain sheet prevents the stacking of graphite domains during high temperature and hinders the shrinkage of pores. The hard carbon has abundant closed pores and large closed pore size; abundant closed pores provide abundant sodium storage sites for the pore filling of sodium ions, and the large closed pore size provides more storage space for the pore filling of sodium ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The Raman images of Example 1 of the present invention and the comparative example prepared by pre-oxidation and without pre-oxidation;
[0032] Figure 2BET diagrams prepared for Examples 1-2 of the present invention and Comparative Examples;
[0033] Figure 3 The pore size distribution diagram of Examples 1-2 and Comparative Examples of the present invention;
[0034] Figure 4 TEM image of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention;
[0035] Figure 5 This is the first charge and discharge curve of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention;
[0036] Figure 6 This is the rate performance of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0037] The present invention uses biomass cotton straw as raw material, adopts mixed salt KOH and K 2 CO 3 As an activator, a hard carbon active precursor with rich pore structure is prepared through activation reaction. A pre-oxidation process is further adopted to graft oxygen onto the graphite domain sheets of the hard carbon active precursor, and then a hard carbon negative electrode material with a large closed pore size is prepared by combining high-temperature crystal transformation and chemical vapor deposition methods. The oxygen-containing graphite domain sheets prevent the stacking of graphite domains during the high temperature process and hinder the shrinkage of the pores. The large-diameter open pores are closed by chemical vapor deposition pore plugging. The hard carbon negative electrode material has a rich number of closed pores and a large closed pore size.
[0038] The large closed-pore hard carbon negative electrode material prepared by the present invention has abundant closed pores and large closed pore diameters; the abundant closed pores provide abundant sodium storage sites for the pore filling of sodium ions, while the larger closed pore diameter provides more storage space for the pore filling of sodium ions; the specific capacity of the platform area is significantly improved while also achieving better kinetic activity, thereby achieving excellent electrochemical performance.
[0039] The present invention provides a method for preparing a large closed-pore hard carbon negative electrode material, comprising the following steps:
[0040] (1) Weighing an appropriate amount of washed and dried cotton stalks, crushing them, and sieving them;
[0041] (2) Mix the sieved cotton straw with KOH and K 2 CO 3 The activators are uniformly mixed according to a certain mass percentage;
[0042] (3) The mixed material obtained in step (2) is subjected to activation reaction in a tube furnace under the protection of argon or nitrogen atmosphere, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use;
[0043] (4) spreading the hard carbon active precursor obtained in step (3) in a uniform thin layer on the bottom of the porcelain boat, placing it in a tube furnace, and performing low-temperature oxidation in an air or oxygen atmosphere to obtain a pre-oxidized hard carbon active precursor;
[0044] (5) placing the pre-oxidized hard carbon active precursor obtained in step (4) in a high-temperature furnace and performing high-temperature crystal transformation in an argon or nitrogen atmosphere to obtain a hard carbon material with a large open pore size; (6) subjecting the hard carbon material with a large open pore size obtained in step (5) to chemical vapor deposition in a mixed gas atmosphere of carrier gas argon and carbon-containing gas to prepare a hard carbon negative electrode material with a large closed pore size.
[0045] Example 1
[0046] (1) Weigh 500 g of washed and dried cotton straw, crush it and sieve it, where the best particle size is about 10 μm. Cotton straw materials with this particle size can have good contact with the mixed salt during the activation and pore-forming process. Therefore, the prepared hard carbon negative electrode material with rich pores exhibits excellent electrochemical properties and fast kinetics.
[0047] (2) Weigh 2 g of sieved cotton straw powder and 1 g of activator (KOH and K 2 CO 3 ) are mixed evenly, cotton straw powder and activator (KOH and K 2 CO 3 ) is 1:2, among which KOH and K 2 CO 3 The mass ratio is 1:1. When the total mass percentage of the activator is 50%, the carbonized material can achieve the optimal activation degree and pore-forming effect. When the total mass percentage of the activator is too low, the activation effect may not be obvious and the pore-forming effect may be poor; when the total mass percentage of the activator is too high, it may lead to excessive activation and complete breakage of the carbon chain, thereby affecting the growth of pores during high-temperature crystal transformation.
[0048] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere, the reaction temperature is 700°C, the reaction time is 5h, the heating rate is 5°C / min, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use.
[0049] (4) Weigh an appropriate amount of hard carbon active precursor and place it in a tubular furnace. In an air atmosphere, heat the temperature to 200°C at a heating rate of 5°C / min for low-temperature pre-oxidation. Keep the temperature for 24 hours and cool to room temperature to obtain a pre-oxidized hard carbon active precursor.
[0050] (5) The pre-oxidized hard carbon active precursor obtained in step (4) is placed in a high temperature furnace, and heated to 1300° C. at a heating rate of 5° C. / min in an argon or nitrogen atmosphere for high temperature crystal transformation, and the temperature is kept for 4 hours to obtain a hard carbon material with a large pore size.
[0051] (6) Place the hard carbon material with large open pores obtained in step (5) in a tube furnace and perform chemical vapor deposition in a mixed atmosphere of argon or nitrogen and benzene at 700°C for 2 hours with a heating rate of 10°C / min. Experimental verification shows that deposition at 700°C for 2 hours can ensure that all large open pores are closed; too low a temperature or too short a time will result in incomplete closure of the open pores. After cooling to room temperature, a hard carbon negative electrode material with large closed pores is obtained.
[0052] The present invention discloses a method for manufacturing a button battery, comprising the following steps: weighing the prepared hard carbon negative electrode material, conductive carbon black (Super C), and binder (PAA) according to a mass ratio of 8:1:1 and mixing them evenly in a mortar, adding an appropriate amount of deionized water as a solvent, stirring evenly with a degassing machine to obtain a paste-like slurry, coating the slurry evenly on an aluminum foil with a coating machine, drying in a vacuum drying oven at 120° C. for 12 hours, and cutting into a circular negative electrode sheet with a diameter of 12 mm for standby use.
[0053] The button cell assembly was carried out in a glove box filled with argon atmosphere. The circular negative electrode and the electrolyte were selected from commercial electrolyte NP-005 (1M NaPF 6 DIGLYME=100Vol%), a metal Na sheet is selected as the counter electrode, and a button cell is assembled.
[0054] In addition, the assembled 2032 button cells were subjected to constant current charge and discharge tests on the Xinwei battery testing system, with the test voltage range being 0.001-2.4V.
[0055] Figure 1 The Raman graphs of Example 1 of the present invention and the comparative example prepared by pre-oxidation and without pre-oxidation are shown in the figure. As can be seen from the figure, the hard carbon after pre-oxidation has an I D / I G It is larger than that without pre-oxidation, which indicates that there are more defects in the graphite domain after pre-oxidation, providing more storage sites for sodium ions.
[0056] Figure 2The BET diagrams prepared in Examples 1-2 and Comparative Examples of the present invention show that, as the pre-oxidation temperature increases, the specific surface area gradually increases, especially when the pre-oxidation temperature is 300 degrees, the specific surface area increases more significantly, reaching 975.4 m 2 / g. Excessive surface oxidation may cause adverse effects and reduce sodium storage performance.
[0057] Figure 3 The pore size distribution diagram of Examples 1-2 and Comparative Examples of the present invention is shown in the figure. It can be seen that after pre-oxidation at 200°C, the micropore size expands from 0.8nm to 1.25nm, and the micropore content also increases significantly. When pre-oxidized at 300°C, the micropore size does not change significantly, but increases slightly, but many mesopores appear at 2.2nm, indicating that excessive pre-oxidation leads to skeleton collapse and produces more mesopores.
[0058] Figure 4 This is a TEM image of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention; it can be clearly seen that there is a pore structure with large pore diameters, which provides a larger space for the storage of sodium ions.
[0059] Figure 5 The first charge-discharge curve of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention; at 20 mA g -1 The charge capacity is as high as 412.4 mAh g -1 , of which the platform capacity contributes 276.9 mAh g -1 , accounting for 67.1%. The high platform capacity is attributed to the abundant number of closed pores with larger pore sizes.
[0060] Figure 6 The rate performance of the large closed-pore hard carbon negative electrode material prepared in Example 1 of the present invention; As can be seen from the figure, at 1A g -1 At the current density, the reversible specific capacity is 311.6 mAh g -1 The excellent rate performance is attributed to the high ion diffusion rate of the closed pores with larger pore sizes.
[0061] Comparative Example 1
[0062] (1) Weigh 500 g of washed and dried cotton straw, crush it and sieve it, where the best particle size is about 10 μm. Cotton straw materials with this particle size can have good contact with the mixed salt during the activation and pore-forming process. Therefore, the prepared hard carbon negative electrode material with rich pores exhibits excellent electrochemical properties and fast kinetics.
[0063] (2) Weigh 2 g of sieved cotton straw powder and 1 g of activator (KOH and K 2 CO 3) are mixed evenly, cotton straw powder and activator (KOH and K 2 CO 3 ) is 1:2, among which KOH and K 2 CO 3 The mass ratio is 1:1. When the total mass percentage of the activator is 50%, the carbonized material can achieve the optimal activation degree and pore-forming effect. When the total mass percentage of the activator is too low, the activation effect may not be obvious and the pore-forming effect may be poor; when the total mass percentage of the activator is too high, it may lead to excessive activation and complete breakage of the carbon chain, thereby affecting the growth of pores during high-temperature crystal transformation.
[0064] (3) The mixed material obtained in step (2) is subjected to an activation reaction in a tubular furnace under the protection of an argon or nitrogen atmosphere, the reaction temperature is 700°C, the reaction time is 5 hours, and the heating rate is 5°C / min. After the reaction is completed, it is cooled to room temperature and taken out, and washed with deionized water to obtain a hard carbon active precursor for use.
[0065] (4) placing the hard carbon active precursor obtained in step (3) in a high temperature furnace, heating the temperature to 1300° C. at a heating rate of 5° C. / min in an argon or nitrogen atmosphere for high temperature crystal transformation, and keeping the temperature for 4 hours to obtain an open-pored hard carbon material.
[0066] (5) The hard carbon material obtained in step (4) is placed in a tubular furnace and subjected to chemical vapor deposition in a mixed atmosphere of argon or nitrogen and benzene at 700°C for 2 hours with a heating rate of 10°C / min. After cooling to room temperature, an appropriate amount of closed-pore hard carbon negative electrode material is obtained.
[0067] (6) Preparation of electrode plates. The hard carbon material, conductive carbon black (Super C), and binder (PAA) were weighed in a mass ratio of 8:1:1 and mixed evenly in a mortar. An appropriate amount of deionized water was added as a solvent. The slurry was prepared by stirring evenly using a degassing machine. The slurry was evenly coated on aluminum foil using a coating machine. The slurry was dried in a vacuum drying oven at 120°C for 12 hours and cut into circular negative electrode plates with a diameter of 12 mm for later use.
[0068] (7) The button cell was assembled in a glove box filled with argon atmosphere. The hard carbon material electrode prepared by the above process steps was used as the negative electrode. The commercial electrolyte NP-005 (1M NaPF6 DIGLYME = 100 Vol%) was used as the electrolyte. The metal Na sheet was used as the counter electrode to assemble the button cell.
[0069] (8) The assembled 2032 button cell was subjected to constant current charge and discharge test on the Xinwei battery test system, with the test voltage range of 0.001-2.4V.
[0070] By analyzing the above comparative examples, it is found that the hard carbon prepared without pre-oxidation treatment has a less porous structure and a smaller pore size; and exhibits poor electrochemical performance as a negative electrode material for sodium ion batteries.
[0071] Example 2
[0072] (1) Weigh 500 g of washed and dried cotton straw, crush it and sieve it, where the best particle size is about 10 μm. Cotton straw materials with this particle size can have good contact with the mixed salt during the activation and pore-forming process. Therefore, the prepared hard carbon negative electrode material with rich pores exhibits excellent electrochemical properties and fast kinetics.
[0073] (2) Weigh 2 g of sieved cotton straw powder and 1 g of activator (KOH and K 2 CO 3 ) are mixed evenly, cotton straw powder and activator (KOH and K 2 CO 3 ) is 1:2, among which KOH and K 2 CO 3 The mass ratio is 1:1. When the total mass percentage of the activator is 50%, the carbonized material can achieve the optimal activation degree and pore-forming effect. When the total mass percentage of the activator is too low, the activation effect may not be obvious and the pore-forming effect may be poor; when the total mass percentage of the activator is too high, it may lead to excessive activation and complete breakage of the carbon chain, thereby affecting the growth of pores during high-temperature crystal transformation.
[0074] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere, the reaction temperature is 700°C, the reaction time is 5h, the heating rate is 5°C / min, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use.
[0075] (4) The hard carbon active precursor obtained in step (3) is placed in a tubular furnace, and in an air atmosphere, the temperature is raised to 150°C at a heating rate of 5°C / min for low-temperature pre-oxidation, and the temperature is kept for 24 hours. After cooling to room temperature, a pre-oxidized hard carbon active precursor is obtained.
[0076] (5) The pre-oxidized hard carbon active precursor obtained in step (4) is placed in a high temperature furnace, and heated to 1300° C. at a heating rate of 5° C. / min in an argon or nitrogen atmosphere for high temperature crystal transformation, and the temperature is kept for 4 hours to obtain a hard carbon material containing open pores.
[0077] (6) The open-pored hard carbon material obtained in step (5) is placed in a tubular furnace and subjected to chemical vapor deposition in a mixed atmosphere of argon or nitrogen and benzene at 700°C for 2 hours with a heating rate of 10°C / min. After cooling to room temperature, a closed-pored hard carbon negative electrode material is obtained.
[0078] Through the analysis of the above Example 2, since the pre-oxidation temperature is too low, resulting in less oxygen connection on the graphite domain sheets, it is impossible to prevent pore shrinkage and pore expansion during high-temperature calcination, thereby failing to obtain a large closed-pore hard carbon negative electrode material.
[0079] Example 3
[0080] (1) Weigh 500 g of washed and dried cotton straw, crush it and sieve it, where the best particle size is about 10 μm. Cotton straw materials with this particle size can have good contact with the mixed salt during the activation and pore-forming process. Therefore, the prepared hard carbon negative electrode material with rich pores exhibits excellent electrochemical properties and fast kinetics.
[0081] (2) Weigh 2 g of sieved cotton straw powder and 1 g of activator (KOH and K 2 CO 3 ) are mixed evenly, cotton straw powder and activator (KOH and K 2 CO 3 ) is 1:2, among which KOH and K 2 CO 3 The mass ratio is 1:1. When the total mass percentage of the activator is 50%, the carbonized material can achieve the optimal activation degree and pore-forming effect. When the total mass percentage of the activator is too low, the activation effect may not be obvious and the pore-forming effect may be poor; when the total mass percentage of the activator is too high, it may lead to excessive activation and complete breakage of the carbon chain, thereby affecting the growth of pores during high-temperature crystal transformation.
[0082] (3) The mixed material obtained in step (4) is activated in a tube furnace under the protection of argon or nitrogen atmosphere, the reaction temperature is 700°C, the reaction time is 5h, the heating rate is 5°C / min, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use.
[0083] (4) The hard carbon active precursor obtained in step (3) is placed in a tubular furnace, and in an air atmosphere, the temperature is raised to 300°C at a heating rate of 5°C / min for low-temperature pre-oxidation, and the temperature is kept at this temperature for 24 hours. After cooling to room temperature, a pre-oxidized hard carbon active precursor is obtained.
[0084] (5) The pre-oxidized hard carbon active precursor obtained in step (4) is placed in a high temperature furnace, and heated to 1300° C. at a heating rate of 5° C. / min in an argon or nitrogen atmosphere for high temperature crystal transformation, and the temperature is kept for 4 hours to obtain a hard carbon material with ultra-large pore size.
[0085] (6) The hard carbon material with ultra-large open pore size obtained in step (5) is placed in a tubular furnace and subjected to chemical vapor deposition in a mixed atmosphere of argon or nitrogen and toluene at 700°C for 3 hours with a heating rate of 10°C / min. After cooling to room temperature, a hard carbon negative electrode material with ultra-large closed pore size is obtained.
[0086] Through the analysis of the above-mentioned Example 3, due to the excessively high oxidation temperature, the skeleton of the active hard carbon precursor is burned and collapsed. Although a large specific surface area can be obtained, the skeleton collapses and the pores are incomplete, resulting in low sodium storage performance.
[0087] Example 4
[0088] (1) Weigh 500 g of washed and dried cotton straw, crush it and sieve it, where the best particle size is about 10 μm. Cotton straw materials with this particle size can have good contact with the mixed salt during the activation and pore-forming process. Therefore, the prepared hard carbon negative electrode material with rich pores exhibits excellent electrochemical properties and fast kinetics.
[0089] (2) Weigh 2 g of sieved cotton straw powder and 1 g of activator (KOH and K 2 CO 3 ) are mixed evenly, cotton straw powder and activator (KOH and K 2 CO 3 ) is 1:2, among which KOH and K 2 CO 3 The mass ratio is 1:1. When the total mass percentage of the activator is 50%, the carbonized material can achieve the optimal activation degree and pore-forming effect. When the total mass percentage of the activator is too low, the activation effect may not be obvious and the pore-forming effect may be poor; when the total mass percentage of the activator is too high, it may lead to excessive activation and complete breakage of the carbon chain, thereby affecting the growth of pores during high-temperature crystal transformation.
[0090] (3) The mixed material obtained in step (2) is activated in a tube furnace under the protection of argon or nitrogen atmosphere, the reaction temperature is 700°C, the reaction time is 5h, the heating rate is 5°C / min, and after the reaction is completed, it is cooled to room temperature and taken out. After washing with deionized water, a hard carbon active precursor is obtained for use.
[0091] (4) The hard carbon active precursor obtained in step (3) is placed in a tubular furnace, and in an air atmosphere, the temperature is raised to 200°C at a heating rate of 5°C / min for low-temperature pre-oxidation, and the temperature is kept at this temperature for 24 hours. After cooling to room temperature, a pre-oxidized hard carbon active precursor is obtained.
[0092] (5) The pre-oxidized hard carbon active precursor obtained in step (4) is placed in a high temperature furnace, and heated to 1300° C. at a heating rate of 5° C. / min in an argon or nitrogen atmosphere for high temperature crystal transformation, and the temperature is kept for 4 hours to obtain a hard carbon material with a large pore size.
[0093] (6) The hard carbon material with large open pore size obtained in step (5) is placed in a tubular furnace and subjected to chemical vapor deposition in a mixed atmosphere of argon or nitrogen and toluene. The deposition is performed at 600°C for 1 hour with a heating rate of 10°C / min. After cooling to room temperature, a hard carbon negative electrode material with large closed pore size is obtained.
[0094] Through the analysis of the above-mentioned Example 4, although the openings with suitable pore sizes are obtained through appropriate pre-oxidation, due to the low deposition temperature and short time, it is still impossible to obtain a hard carbon negative electrode material with large closed pore sizes and excellent performance.
[0095] One of the difficulties in the preparation process of the large closed-pore hard carbon negative electrode material of the present invention is that it is important to note that during the pre-oxidation process, air or oxygen must fully contact the hard carbon active precursor, and must be spread on the bottom of the porcelain boat in a thin layer with air permeability to ensure sufficient pre-oxidation. If the layer is too thick, the pre-oxidation is insufficient, and the agglomeration of particles will also cause insufficient pre-oxidation. At the same time, too low a temperature will prevent oxygen from being grafted onto the carbon, and too high a temperature will cause oxygen or burn part of the carbon. Therefore, appropriate pre-oxidation conditions must be ensured.
[0096] The chemical vapor deposition reaction in step (4) of the present invention is also the key to obtaining large closed-pore hard carbon negative electrode materials. If the temperature is too low, the graphitization degree of the pore-filling carbon is too low, resulting in serious defects; if the temperature is too high, the graphitization degree of the pore-filling carbon is too high, resulting in a small interlayer spacing. The appropriate pore-blocking temperature range is 600-900°C. The specific surface area of the large closed-pore hard carbon negative electrode material is 2-10m 2 / g. The large closed-pore hard carbon material can be used as a negative electrode material for sodium ion batteries. Experiments have shown that the large closed-pore hard carbon negative electrode material prepared by the present invention is used as a negative electrode material for sodium ion batteries. Its larger closed-pore pore size provides more storage space for pore filling of sodium ions, significantly improving the specific capacity of the platform area, thereby achieving excellent electrochemical performance.
[0097] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a large closed-pore hard carbon negative electrode material, characterized in that: The following steps are involved: (1) Weighing an appropriate amount of washed and dried cotton stalks, crushing them, and sieving them; (2) mixing the sieved cotton straw and an activator consisting of KOH and K2CO3 in a certain mass percentage; (3) subjecting the mixed material obtained in step (2) to an activation reaction in a tube furnace under the protection of an argon or nitrogen atmosphere, and taking it out after cooling it to room temperature after the reaction is completed; washing it with deionized water to obtain a hard carbon active precursor for use; (4) spreading the hard carbon active precursor obtained in step (3) in a uniform thin layer on the bottom of the porcelain boat, placing it in a tube furnace, and performing low-temperature oxidation in a pre-oxidation atmosphere to obtain a pre-oxidized hard carbon active precursor; (5) placing the pre-oxidized hard carbon active precursor obtained in step (4) in a high temperature furnace and performing high temperature crystal transformation under an argon or nitrogen atmosphere to obtain a hard carbon material with a large pore size; (6) The hard carbon material with large open pore size obtained in step (5) is subjected to a chemical vapor deposition reaction in a mixed gas atmosphere of carrier argon and carbon-containing gas to prepare a hard carbon negative electrode material with large closed pore size.
2. The preparation method according to claim 1, characterized in that: The particle size of the cotton straw powder is 2-20 microns.
3. The preparation method according to claim 1, characterized in that: In the step (2), the mass percentage of cotton straw to activator is 25%-100%, wherein the mass ratio of KOH to K2CO3 is 1:
1.
4. The preparation method according to claim 1, characterized in that: The activation reaction temperature in step (3) is 700-850°C, the heating rate is 5-10°C / min, and the reaction time is 2-5h.
5. The preparation method according to claim 1, characterized in that: In the step (4), the oxidation temperature is 150-300° C., the heating rate is 5-10° C. / min, and the pre-oxidation time is 12-24 h.
6. The preparation method according to claim 1, characterized in that: In the step (5), the pre-oxidized hard carbon active precursor is placed in a high temperature furnace for high temperature reaction, the reaction temperature is 1200-1600° C., the reaction time is 4-6 hours, and the heating rate is 5-10° C. / min.
7. The preparation method according to claim 1, characterized in that: The carrier gas in step (6) is argon or nitrogen, the gas flow rate is 150-300 mL / min, and the volume concentration of the carbon-containing gas in the mixed gas is not less than 5%.
8. Large closed-pore hard carbon negative electrode material, characterized by: The material is obtained by the preparation method described in any one of claims 1 to 7; wherein the specific surface area of the large closed-pore hard carbon negative electrode material is 2-10 m 2 / g, and has a large closed pore size; the hard carbon active precursor has a high microporosity.
9. A sodium ion battery, characterized in that: The invention comprises a negative electrode material for a sodium ion battery, wherein the negative electrode material is a large closed-pore hard carbon negative electrode material prepared by the preparation method described in any one of claims 1 to 7.
10. A method for manufacturing a button battery, characterized by: Step 1: Weigh the large closed-pore hard carbon negative electrode material, conductive carbon black (Super C), and binder (PAA) according to claim 8 in a mass ratio of 8:1:1 and mix them evenly in a mortar, add an appropriate amount of deionized water as a solvent, use a degassing machine to stir evenly to obtain a slurry, use a coating machine to evenly coat the slurry on aluminum foil, dry it in a vacuum drying oven at 120°C for 12 hours, and cut it into a circular negative electrode sheet with a diameter of 12 mm for standby use; Step 2: Assemble button cells in a glove box filled with argon atmosphere. Use commercial electrolyte NP-005 (1M NaPF6 DIGLYME=100Vol%) as electrolyte and metal Na sheet as counter electrode to assemble button cells.
Citation Information
Patent Citations
Preparation method of waste biomass hard carbon negative electrode material for sodium ion battery
CN115417397A
Preparation method and application of sodium ion battery hard carbon material
CN116947038A
Method for preparing hard carbon negative electrode material rich in closed pores from porous carbon and application of hard carbon negative electrode material
CN118239487A
Cited By
Hard carbon negative electrode material and preparation method thereof
CN122608003A